Reformulation of Corporate Criminal Liability for Environmental Pollution and Degradation in the Mining Sector in Indonesia - Rihat Hutabarat (Journal Customary Law, 2026)
This study aims to analyze the Indonesian positive law governing corporate criminal liability for environmental crimes arising from mining activities, assess the effectiveness of its enforcement, and formulate a more progressive and relevant reconstruction model. The research problem stems from the gap between legal norms, which have formally recognized corporations as subjects of criminal law, and law enforcement practices, which remain predominantly reliant on administrative and civil instruments. This research employs a normative-empirical legal method using statutory, conceptual, case, and comparative approaches. The data were analyzed qualitatively through descriptive-analytical, evaluative, comparative, and prescriptive stages. The findings indicate that the Law on Environmental Protection and Management has provided a legal basis for imposing criminal liability on corporations; however, its implementation remains weak due to the difficulties in proving corporate fault, the limited technical capacity of law enforcement officials, weak inter-agency coordination, and the strong influence of economic and political interests. A comparative analysis of the legal frameworks of the United States, the United Kingdom, and Australia demonstrates that the approaches of corporate culture, strict liability, and corrective additional criminal sanctions are more effective in holding corporations accountable. Accordingly, this study proposes a reconstruction of corporate criminal liability that positions the corporation as the principal offender through fault attribution based on corporate culture, the strengthening of strict liability for certain environmental offences, and the imposition of ecological restoration, concession disqualification, publication of judgments, and compliance monitorship. This model is expected to strengthen ecological justice, protect affected communities, and ensure environmental sustainability.